Reviewing Microbial Behaviors in Ecosystems Leading to a Natural Quorum Quenching Occurrence - Zapata,Laura Sierra (2017)
ABSTRACT Quorum sensing is considered one of the most important discoveries in cell-to-cell communication. Although revealed in Bacteria, it has been identified as well as a mechanism present in the other two domains, Eukaryota and Archaea. This phenomenon consists mainly of an exchange and sensing of "words" produced by each cell: chemical signals known as autoinducers. The process takes places at high cell densities and confined environments, triggering the expression of specific genes that manifest in a determined phenotype. Quorum sensing has a fundamental importance in the organisms' fitness in natural ecosystems since it activates many of the traits needed by cells to survive under specific conditions, and thus a wide variety of chemical signals, which are detailed throughout the review, have evolved in response to the needs of an organism in the ecosystem it inhabits. As a counterpart, derived from the natural occurrence of quorum sensing, comes it's antagonistic process named quorum quenching. Acting in the exact opposite way, quorum quenching interferes or degrades the autoinducers confusing and stopping communication, hence affecting transcriptional regulation and expression of a specific phenotype. The main reasons for stopping this mechanism go from fading their own signals when perceiving scarce nutrients conditions, to degrading competitors' signals to take advantage in the ecosystem. Some of the most studied purposes and means known up to date to be used by cells for making quorum quenching in their ecosystems is what will be discussed along this review, offering information for future works on quorum quencher molecules bioprospection.